Public awareness, knowledge, and attitude regarding proper disposal of unused medicines and associated factors in Gondar city, northwest Ethiopia - Tegegne, Addisu Afrassa; Genet, Gebremariam; Workie Limenh, Liknaw; Yohannes, Lamrot; Mohammed Seid, Abdulwase; Alemayehu, Tekletsadik Tekleslassie; Ayenew, Wondim; Simegn, Wudneh (Frontiers in Public Health, 2024)
Background Proper disposal of unwanted medicines, in addition to reducing wastage, has a positive impact on the environment and public health. Improper disposal of medications increases the risk of accidental poisonings, particularly among children. This study aimed to assess the level of knowledge, attitudes, and awareness regarding the proper disposal of unused medicines in Gondar city, northwest Ethiopia. Method From 30 July to 30 August 2023, a community-based cross-sectional study was conducted among the public in Gondar city. The data were gathered using the Kobo toolbox, exported into an Excel sheet, and then analyzed using SPSS version 27. Multivariate and bivariate binary logistic regressions were performed. A p-value of 0.05 with a 95% confidence interval (CI) was used to determine statistical significance. Result From 786 study participants, the overall knowledge and attitude of the community toward the proper disposal of unused medicines were 42.6 and 42.9%, respectively. Factors identified in this study included ages between 19 and 25 [AOR = 6.91, 95% CI: (3.45, 13.84); education level: secondary [AOR = 11.82, 95% CI: (1.01, 3.29)] and college and above [AOR = 5.68, 95% CI: (2.25, 14.30)]; prior information [AOR = 6.41; 95% CI: (4.02, 10.22)]; and good attitudes [AOR = 2.11; 95% CI: (1.47, 3.02)]] as factors associated with good knowledge toward proper disposal of unused medicines. In addition, receiving information [AOR = 1.86 95% CI: (1.22, 2.86)], taking medication in the past 6 months [AOR = 1.61, 95% CI: (1.09, 2.38)], and being knowledgeable [AOR = 2.07 95% CI: (1.46, 2.94)] were factors contributing to positive attitudes toward the disposal of unused medicines among the general public. Furthermore, approximately 369 participants (46.9%) in our study lacked awareness about the harmful effects of disposing of unused medicine in regular waste. Conclusion A relatively low level of knowledge and attitudes about the proper disposal of unused medications is present in the community. In this regard, a well-coordinated and methodical public awareness campaign is recommended to disseminate information and promote the appropriate disposal of unused medications.